PELAKSANAAN TUGAS SATUAN POLISI PAMONG PRAJA DALAM MENERTIBKAN PEDAGANG MOBIL KELILING - Fadil Muhammad (Universitas Riau, 2015)
Duties Civil Service Police Unit in the discipline Roving Car Dealer. This study aims to identify and describe the implementation of tasks Civil Service Police Unit in the discipline around the car dealer in Pekanbaru. The method used is descriptive and quantitative methods; Samples that Satpol Members of the Civil Service and car dealers around numbering 70 people. Data collection techniques were questionnaires, observations and interviews. Data analysis is quantitative descriptive. Results of research on the implementation of tasks Civil Service Police Unit in the discipline around the car dealer in Pekanbaru is “Good Enough”. Barriers were found in this study is the absence of regulations governing the particulars of car dealers around, while the current authority of the municipal police of Pekanbaru in to curb car dealers around only be guided by the Regional Regulation Pekanbaru on Public Order so that it makes the role of municipal police Pekanbaru city is very limited.